2019
DOI: 10.3389/fonc.2019.00338
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Adrenocortical Oncocytoma: Case Report of Five Cases and Review of the Literature

Abstract: Objective: To investigate the diagnosis and treatment of adrenocortical oncocytoma, and have a literature of review. Materials and Methods: The clinical data of 5 cases of adrenocortical oncocytoma treated in our hospital was retrospectively analyzed. The clinical manifestations, imaging examination, endocrine examination, and pathological results were analyzed respectively. Results: Oncocytic adrenocortical neoplasms are extremely rare. Oncocytic adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…The adrenal tumor pathology showed oncocytic neoplasm positive for chromogranin, synaptophysin, and S100, and negative for inhibin and calretinin, consistent with pheochromocytoma. Adrenocortical oncocytic neoplasms are rare, with only a few cases reported [ 18 ]. They are rarely functional, and all reported cases were benign.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal tumor pathology showed oncocytic neoplasm positive for chromogranin, synaptophysin, and S100, and negative for inhibin and calretinin, consistent with pheochromocytoma. Adrenocortical oncocytic neoplasms are rare, with only a few cases reported [ 18 ]. They are rarely functional, and all reported cases were benign.…”
Section: Discussionmentioning
confidence: 99%
“…Majority are non-functional (66%–83%) and are diagnosed incidentally 16 17. There have been reports of OANs secreting cortisol,18–20 aldosterone,21 combined cortisol and aldosterone,22 and combined cortisol and steroid precursors 23 Online supplemental table 1. summarises the characteristics of 246 reported cases of OANs in English.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Adrenal oncocytomas are extremely rare, with nearly 200 published cases since Kakimoto et al reported the first case in 1986. 5,6 The mechanisms for oncocytosis are not well understood and there are two theories: the first defends that mitochondria proliferation is a result of a genetic mutation and the second that it is a consequence of an epigenetic event resulting from cellular hypoxia. 10,11 Adrenal oncocytoma can occur in a large age range (15-77 years), more frequently in women (2.5:1.0), in the left adrenal gland (3.5:1.0), without known risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Adrenal oncocytomas are extremely rare, with nearly 200 published cases since Kakimoto et al reported the first case in 1986. 5,6 The detection of adrenal oncocytomas is mostly incidental since they are frequently non-functional; however, biochemical analyses are recommended to exclude functional status. 7 Imaging is not a reliable method of diagnosis for oncocytomas as they can display features often present in other tumours, such as carcinoma; histological analysis is required for an accurate diagnosis.…”
mentioning
confidence: 99%